Investigating preventive-medicine consultations in first-opinion small-animal practice in the United Kingdom using direct observation - Robinson, N.J.; Brennan, Marnie L.; Cobb, M.; Dean, Rachel S. (Elsevier, 2016)
Preventive-medicine consultations account for a large proportion of the veterinary caseload and previous research has suggested these consultations are fundamentally different from those in which the animal is presented for a specific health problem. There has been recent controversy around some aspects of preventive medicine for cats and dogs, and the full health benefits of the preventive-medicine consultation remain unclear. The aim of this study was to compare characteristics of the consultation and the problems discussed during the consultation between preventive-medicine consultations and other types of consultations.